Evaluation of Subcortical Structure Volumes in Patients with Non-Specific Digestive Diseases - Katarzyna Skrobisz; Grazyna Piotrowicz; Agata Rudnik; Patrycja Naumczyk; Agnieszka Sabisz; Karolina Markiet; Edyta Szurowska (Diagnostics, 2022)
(1) Background: To evaluate volume of subcortical structures such as hippocampus, globus pallidus, putamen, thalamus, nucleus accumbens, amygdala, caudate in patients with non-specific digestive diseases (functional dyspepsia—FD, irritable bowel syndrome—IBS) and non-specific inflammatory bowel diseases—IBD (colitis ulcerosa and Crohn’s disease) in comparison to healthy control group (CON). (2) Material: The analysis included data obtained from 57 patients (FD-18, IBS-20, IBD-19) and 19 persons in control group. Both groups underwent examination in a 3T scanner (Achieva TX Philips Healthcare). (3) Results: Significant differences between the IBD group and Control group in volume of left thalamus and IBD group vs Control group in volume of right thalamus. (4) Conclusions: The brain-gut axis hypothesis explains connection between biological behavior, emotions and cognitive functions in patients with gastrointestinal disease. We found that there is a difference between volume of thalamus in IBD patients in comparison to both IBS and control group and it occurred to be smaller. Excess inflammation can be linked with psychological disorders like depressive symptoms, sleep difficulties and/or fatigue. Therefore, there is a need for using treatment both for depressive symptoms and IBD to reduce the causes and effects of inflammation.